2007
DOI: 10.1016/j.lwt.2006.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fining treatment and storage temperature on the quality of clarified banana juice

Abstract: The clarified banana juice was subjected to different treatment namely bentonite, combination of gelatin and bentonite and control and stored at 4, 25 and 37 1C for 24 weeks. The effects of fining treatment, storage temperature and storage time on turbidity, total polyphenol, browning index, microbiological, and sensory quality of clarified banana juice were evaluated during storage. Fining treatment, storage temperature and storage time had a significant (po0.001) effect on turbidity, total polyphenol and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…() and Lee et al . () reported a reduction in turbidity of apple and banana juices using combination of bentonite and gelatin and using two treatments of bentonite and combination of bentonite and gelatin, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Lee et al . () reported a reduction in turbidity of apple and banana juices using combination of bentonite and gelatin and using two treatments of bentonite and combination of bentonite and gelatin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al . () also found a significant ( P < 0.001) decrease in turbidity of banana juice by clarification with bentonite and a combination of gelatin and bentonite. Alper et al .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the heat treated samples exhibited a significant increase in turbidity during the whole storage period (p b 0.05). Lee, Yusof, Hamid, and Baharin (2007) reported that the turbidity increment in the juice during storage could arise from the effect of protein and polyphenol complexes. The change in turbidity of the LMJ blend juice can also be related to the residual PME activity after the treatments (Rivas et al, 2006).…”
Section: Multivariate Statistical Analysis Of Physicochemical Propertmentioning
confidence: 99%
“…A decrease in lightness and transmittance values was observed for all the clarified samples during storage. Previous studies of clarified banana juice (Tajchakavit et al ., ; Lee et al ., ) and clarified apple juice also showed that an increase in turbidity was found during storage. Fining treatment removed the potential contributors to haze (proteins and polyphenols) from solutions, thus resulting in less formation of haze.…”
Section: Resultsmentioning
confidence: 97%